Chemoenzymatic and microbial dynamic kinetic resolutions - Azlina, Harun Kamaruddin; Mohamad Hekarl, Uzir; Hassan Y., Aboul-Enein; Hairul Nazirah, Abdul Halim (Wiley-Liss, Inc, 2009)
Link to publisher's homepage at http://www3.interscience.wiley.com/journal/37532/home?CRETRY=1&SRETRY=0